Quem não sonhou em ser uma jogadora de futebol? Documentário sobre histórias e vivências de mulheres que jogam futebol - Santos, Aline Guerra (2022)
This work presents a documentary with the theme of Women's Football, its characters, practice and history; in addition, it seeks to analyze, present and discuss the representation of the modality in the media throughout history. Using concepts such as language and representation and research on gender and visibility of women in sport and media platforms. How does the journalistic capacity to pay attention to certain historical narratives work, and what role does the media assume when privileging indicated memories and spaces in place of others.